Analysis Of Potential Income Manipulation Using Beneish M-Score Model - Septian, Defel; Khairunnisa; Indrawan, Aril; Irsa Suryaputra, Muhammad (Islamic Accounting Journal, 2026)
Objective & object: This research aims to analyze the potential for earnings manipulation in insurance sector companies listed on the Indonesia Stock Exchange (IDX) using the Beneish M-Score Model. The research variables include the eight Beneish financial ratios, namely Days Sales in Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Sales, General and Administrative Expenses Index (SGAI), Leverage Index (LVGI), dan Total Accruals to Total Assets (TATA) of annual financial reports of insurance companies. Methods: This research uses a descriptive quantitative approach with secondary data for the period 2022–2024. Data analysis techniques were carried out by calculating the Beneish M-Score to identify indications of earnings manipulation, where an M-Score value of > –2.22 indicates potential manipulation. Results & Conclusions: Results show that some insurance companies, such as JMAS, MREI, TUGU, ABDA, and ASRM, have M-Score values above the threshold, which indicates potential earnings manipulation. The trend in the last three years shows a general increase in M-Score values, especially in the 2023–2024 period. This research supporting the hypothesis that there are indications of earnings manipulation practices in the Indonesian insurance sector. These findings strengthen agency theory and emphasize the importance of supervision and the implementation of effective corporate governance to maintain the integrity of financial reporting. Limitations: Beneish M-Score model relies solely on financial ratios from the company's annual reports, thus not taking into account qualitative factors such as changes in management policy, internal audit practices, or the influence of corporate governance. Non-use of cross-sector comparisons, which could help to see if similar practices occur in other industries with different regulatory and economic pressures. Implications: This study strengthens agency theory and the literature on earnings management, particularly within the highly regulated financial sector such as insurance. The findings indicate that despite stringent regulatory oversight, earnings manipulation remains a possibility. This contributes to the development of earnings manipulation detection models in the financial services sector, especially through the quantitative analysis of the Beneish M-Score. Furthermore, it serves as a critical reminder to enhance the effectiveness of financial statement oversight and auditing.